High-Intensity Inspiratory Muscle Training Improves Scalene and Sternocleidomastoid Muscle Oxygenation Parameters in Patients With Weaning Difficulties: A Randomized Controlled Trial - Van Hollebeke, Marine; Poddighe, Diego; Clerckx, Beatrix; Muller, Jan; Hermans, Greet; Gosselink, Rik; Langer, Daniel; Louvaris, Zafeiris (Frontiers in Physiology, 2022)
Background: Critically ill patients who have difficulties weaning from the mechanical ventilator are prone to develop respiratory muscle weakness. Inspiratory muscle training (IMT) can improve respiratory muscle strength. Whether IMT can improve extradiaphragmatic muscle oxygenation is unknown. Aim: To compare changes in muscle oxygenation of extradiaphragmatic inspiratory muscles during a standardized task between patients with weaning difficulties who received either high-intensity IMT (intervention) or sham low-intensity IMT (control). Method: 41 patients performed daily IMT sessions (4 sets, 6–10 breaths) until weaning success or for 28 consecutive days. The training load was progressively adjusted in the intervention group (n=22) to the highest tolerable load, whilst the control group (n=19) kept training at 10% of their baseline maximal inspiratory pressure (PImax). Breathing characteristics (i.e. work and power of breathing, PoB), respiratory muscle function (i.e. PImax and forced vital capacity) were measured during a standardized loaded breathing task against a load of 30% of baseline PImax before and after the IMT period. In addition during the same loaded breathing task, absolute mean and nadir changes from baseline in local scalene and sternocleidomastoid muscles fractional oxygenation (Δ%StiO2) (an index of oxygen extraction) and nadir ∆%StiO2 normalized for the PoB were measured by near-infrared spectroscopy. Results: At post measures, only the intervention group improved mean PoB compared to pre measures (Pre: 0.42±0.33 watts, Post: 0.63±0.51watts, p-value<0.01). At post measures, both groups improved nadir scalene muscles StiO2% normalized for the mean PoB (∆StiOnadir%/watt) significantly compared to pre measurements and the improvement was not significant different between groups (p-value=0.40). However, at post measures, nadir sternocleidomastoid muscle StiO2% normalized for power output (∆StiOnadir%/watt) was significantly greater improved in the intervention group (mean difference: +18.4, 95%CI:-1.4; 38.1) compared to the control group (mean difference: +3.7, 95%CI: -18.7; 26.0, between group p-value<0.01). Both groups significantly improved PImax (Intervention: +15±13cmH2O p-value<0.01, Control: +13±15 cmH2O p-value<0.01). Forced vital capacity only significantly improved in the intervention group (+0.33±0.31L p<0.01) report also change in control group. Conclusion: This exploratory study suggests that high-intensity IMT induces greater improvements in extradiaphragmatic inspiratory muscle oxygenation compared to low-intensity IMT in patients with weaning difficulties.